Qualidade de vida no trabalho dos servidores administrativos de uma instituição federal de ensino superior - (:unkn) unknown (Universidade Federal de Goiás, 2014)
Whereas the work has occupied more time in people's lives and the prospect that the conflicts and diseases may result from work activity in this context, research related to Quality of Life at Work (QLW) are becoming important in organizational studies . Using an identification model of Quality of Life at Work levels, already validated - Walton model - this study aimed to evaluate the QLW administrative employees of a Federal Institution of Higher Education (IFES). Similarly, we attempted to verify the perception of servers compared to the set of attributes associated with satisfaction with the conditions offered by the organization to perform its functions, and identify the perception of administrative staff regarding the actions of the institution in respect to: working conditions, work organization, Social Integration, Participation, Health, Compensation, Communication and Organization Image. Therefore, we carried out a descriptive and mixed study with a qualitative and quantitative approach, through online questionnaire based in Walton model, adapted and validated by Frossard (2009) with simple causal probability sample consisting of 76 administrative staff in several areas and four (4) managers from different administrative sectors of IFES, including Direction and Coordination courses, which took place with interviews with semi-structured, enabling discussion of the possible forms of assistance and analysis of the conditions and intentions in QLW shares organization. The results revealed that, in general, the QLW level of administrative staff, based on the model used, has diversified aspects. We have found relevant and positive satisfaction ratings, such as autonomy, security, infrastructure and interpersonal relationships. However, indicators such as health, compensation, communication and organizational image directly revealed considerable dissatisfaction index, indicating the need for greater attention and investment.
Quality of life at work servers administrative a institution of higher education
Keywords: Qualidade de vida; Qualidade de vida no trabalho; Saúde ocupacional; Quality of life; Quality of working life; Occupational health; ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS